Konteks Kultural Percakapan Mahasiswa dan Dosen (Kajian Pragmati Siber) - Siti Maisaroh; M. Bayu Firmansyah; Ilmiyatur Rosyidah (BADAN PENERBIT STIEPARI PRESS, 2024)
The aim of this research is to analyze the cultural context of student and lecturer conversations (cyber pragmatics study). The theory used in this research is the cultural context theory in cyber pragmatics proposed by Rahardi (2020). This research is descriptive qualitative in nature. The method used is analyzing and using note-taking techniques. The data source in this research is from conversations via WhatsApp social media in the even semester thesis course, namely the eighth semester class of 2020, Department of Indonesian Language and Literature Education. The data was taken starting on January 28 2024 and limited to July 18 2024. Researchers succeeded in finding the cultural context of student and lecturer conversations (cyber pragmatics studies) on WhatsApp social media from 88 data, with details: (1) ethical dimensions of each For each indicator, namely, 84 data were found about student conversations that applied manners, 58 data were found about student conversations that applied manners, and 80 data were found about student conversations that applied customs. (2) the aesthetic dimension was found in 58 data, (3) the conscience dimension was found in 13 data.